Globalization and Academic Research: The Case of Sustainability Marketing. (January 2014) - Purani, Keyoor; Sahadev, Sunil; Kumar, Deepak S.
The impact of globalization on academic research is undeniable. This impact is more pertinent and strongly felt in the academic field of marketing. The pattern of this impact can be easily discerned from the trends in academic publishing in marketing such as more globalized representation of university affiliation of authors or the type of topics that dominate academic publishing in the field of marketing. In this article, through systematic analysis, one such trend is observed. The subjects covered by articles published in the 10 important marketing journals are analyzed in order to measure the extent to which these journals cover sustainability and related issues. Minimal representation of sustainability-based issues in the academic papers published in the most important marketing journals is argued to be closer to the idea of 'Academic Capitalism' in light of globalization. Considering the argument that sustainability and related issues often pose difficult questions to the mainstream schools of thought in the field of marketing, the minimal coverage given to sustainability-based issues should be perceived as reflecting the general lack of interest in conducting research in sustainability. The article discusses implications as well as pathways for future research.